Delineating spatial use combined with threat assessment to aid critical recovery of northeast Australia’s endangered hawksbill turtle, one of western Pacific's last strongholds - Madden Hof, Christine A.; Smith, Caitlin; Miller, Simon; Ashman, Kita; Townsend, Kathy A.; Meager, Justin (Frontiers in Marine Science, 2023)
The current rate of decline in the globally significant western Pacific hawksbill turtle nesting population on Milman Island on the northern Great Barrier Reef (neQLD) suggests that it could be functionally extinct within a decade. Yet a poor understanding of the relative importance and spatial distribution of threats to this population has been a major impediment to recovery actions. For the first time, we assess all threats to the neQLD stock using a combination of a post-hatchling dispersal model, new satellite tracking of post-nesting migrations and a comprehensive review of existing data. We overlay migration routes and foraging areas from the satellite tracking data with spatially referenced threat layers to analyse threat exposure. We found all tracked hawksbills remained in Australian waters, with migration to foraging areas in Queensland including western Cape York to western Torres Strait (n = 8), and eastern Cape York to eastern Torres Strait (n = 5). These results underscore the critical importance of foraging habitats in Queensland (particularly western Queensland) to the Millman Island nesting population. In contrast, the Lagrangian post-hatchling dispersal model predicted a concentration of turtles in the Torres Strait to Gulf of Papua region, with most final positions in Australian waters (63%), followed by Papua New Guinea (31%), Solomon Islands (3%), Indonesia (2%), Vanuatu (0.49%), New Caledonia (1%). Even though 37% of post-hatchling turtles were predicted to recruit to foraging areas outside of the Australian Exclusive Economic Zone (EEZ), none of the 25 turtles tracked left the Australian EEZ (13 in this study and 12 previously). This suggests that survival to breeding is low for turtles outside of the Australian EEZ, but other explanations are discussed. No single pervasive threat was identified in the threat risk assessment however, fisheries (bycatch/ghost gear) interactions, direct harvesting and climate change were considered to have the potential to impede recovery or result in further decline in the population. Fisheries and harvesting should be the priorities for immediate management actions. The lack of spatial protection in foraging habitats in western Queensland was identified as a major policy gap requiring immediate attention if this population’s trajectory is to be reversed and remain one of western Pacific’s strongholds.